2015
DOI: 10.1007/s10103-015-1742-5
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-loaded macrophage-mediated photothermal therapy: potential for glioma treatment

Abstract: Gold-based nanoparticles have been used in a number of therapeutic and diagnostic applications. The purpose of this study was to investigate the efficacy of gold–silica nanoshells (AuNS) in photothermal therapy (PTT) of rat gliomas. Rat alveolar macrophages (Ma) were used as nanoparticle delivery vectors. Uptake of AuNS (bare and PEGylated) was investigated in Ma. AuNS were incubated with Ma for 24 h. Phase contrast microscopy was used to visualize the distribution of loaded Ma in three-dimensional glioma sphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 24 publications
5
68
0
1
Order By: Relevance
“…Accordingly, they may preferentially penetrate into hypoxic regions within the tumor mass [14,15]. Most previous studies were confined to in vitro studies [16]. In our last study, we confirmed the possibility of using macrophages as live vectors for the delivery of nanoparticles and identified the optimal conditions for PTT to selectively kill cancer cells around nanoshell (NS)-loaded macrophages in an in vitro model [17].…”
Section: Introductionsupporting
confidence: 65%
“…Accordingly, they may preferentially penetrate into hypoxic regions within the tumor mass [14,15]. Most previous studies were confined to in vitro studies [16]. In our last study, we confirmed the possibility of using macrophages as live vectors for the delivery of nanoparticles and identified the optimal conditions for PTT to selectively kill cancer cells around nanoshell (NS)-loaded macrophages in an in vitro model [17].…”
Section: Introductionsupporting
confidence: 65%
“…21 It has been published that inflammatory tumor-associated macrophages and cancer-associated fibroblasts have high uptake toward gold NPs. [44][45][46] Our results showed complete clearance of the tumor with no relapse or metastasis. Therefore, we expect that PPTT has a significant effect on a tumor's microenvironment, which is most likely related to the high uptake of AuNRs and therefore consistent with the higher photothermal response for cancer-associated fibroblasts and inflammatory tumorassociated macrophages in the tumor microenvironment.…”
supporting
confidence: 57%
“…Figure S1 sPB of 3 nm auNP. UV-Vis spectrum of 3 nm auNP measured in chcl 3 . Abbreviations: auNPs, gold nanoparticles; sPB, surface plasmon band; UV-Vis, ultraviolet-visible.…”
Section: Resultsmentioning
confidence: 99%
“…1 h NMr spectra of 3 nm auNP in cDcl 3 . Abbreviations: auNPs, gold nanoparticles; NMr, nuclear magnetic resonance.…”
Section: Figure S2mentioning
confidence: 99%
See 1 more Smart Citation